2020
DOI: 10.1101/2020.07.14.202382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortico-subcortical functional connectivity profiles of resting-state networks in marmosets and humans

Abstract: Understanding the similarity of cortico-subcortical networks topologies between humans and nonhuman primate species is critical to study the origin of network alternations underlying human neurological and neuropsychiatric diseases. The New World common marmoset (Callithrix jacchus) has become popular as a non-human primate model for human brain function. Most marmoset connectomic research, however, has exclusively focused on cortical areas, with connectivity to subcortical networks less extensively explored. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 71 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…2 for all derived network maps). Seven statistically significant networks were found: three somatosensory networks (SMNs), a default mode network (DMN), a primary visual network (VISp), a high-order visual network (VISh), and a salience network (SAN)-networks previously confirmed to be present in the resting marmoset 28,37,48 . Inter-brain synchronous connectivity with a visible conspecific.…”
Section: Resultsmentioning
confidence: 94%
“…2 for all derived network maps). Seven statistically significant networks were found: three somatosensory networks (SMNs), a default mode network (DMN), a primary visual network (VISp), a high-order visual network (VISh), and a salience network (SAN)-networks previously confirmed to be present in the resting marmoset 28,37,48 . Inter-brain synchronous connectivity with a visible conspecific.…”
Section: Resultsmentioning
confidence: 94%
“…frontal eye field, LIP) even under resting-state (Fox et al, 2005). In marmosets, one of the core regions of the DMN is the cortex surrounding the IPS (Belcher et al, 2013; Hori et al, 2020b; Liu et al, 2019). A functional imaging study in marmosets showed that these areas were deactivated during a visual stimulation task relative to the period when a black screen was presented (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A functional imaging study in marmosets showed that these areas were deactivated during a visual stimulation task relative to the period when a black screen was presented (Liu et al, 2019). On the other hand, the area surrounding the marmoset IPS have also been linked to the attention-like frontoparietal network by several RS-fMRI studies (Ghahremani et al, 2016;Hori et al, 2020b). It is also known that electrical microstimulation in the areas surrounding the IPS evoke saccadic eye movements (Ghahremani et al, 2019) and that single neurons in the region show neural correlates for the gap effect in saccadic eye movement tasks (Ma et al, 2020).…”
Section: Functional Correspondence In Parietal and Motion-selective Vmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strong overlaps in SI connectivity maps were found in pulvinar and VP suggesting that parts of these areas process tactile information regardless of the stimulated body part. VP has been shown to be strongly connected to 3a and 3b (Brysch et al, 1990;Krubitzer and Kaas, 1992;Huffman and Krubitzer, 2001b;Hori et al, 2020b). SII connectivity maps showed mainly overlap between body representations.…”
Section: Somatotopy In Subcortical Areas: Thalamus and Putamenmentioning
confidence: 95%